Absolute carnage ebook - Cates, Donny (Absolute Carnage (2019)., 2020)
Collects Absolute Carnage (2019) #1-5 and material from Free Comic Book Day 2019 (Spider-Man/Venom) #1. Paint the town red - blood red! Carnage, the psychotic offspring of Venom, has returned — and he plans to slaughter everyone who's ever worn a symbiote! Cletus Kasady has skirted the periphery of the Marvel Universe for months, but now he stands poised to make his grand return to New York — and he's more powerful than ever! To make matters worse, a new player is on the board, and it's not who you'd expect! Spider-Man and Venom must face down Carnage's madness, but things aren't looking good. Barely able to escape with their lives, the uneasy allies have no choice but to drag a slew of other heroes into Carnage's crosshairs. And the hard truth is that not everybody will make it out of this conflict in one piece - if they make it out at all!